Intracranial vascular imaging detects arterial wall abnormalities in persons with treated HIV infection. (1st January 2022) - Chow, Felicia C.; Callen, Andrew; Arechiga, Victor; Saloner, David; Narvid, Jared; Hsue, Priscilla Y.
Abstract : Objective: Although a substantial proportion of ischemic strokes in persons with HIV infection (PWH) is related to large artery disease, studies evaluating elevated cerebrovascular risk in PWH have focused primarily on microvascular disease. We compared the burden of intracranial large artery disease on vessel wall MRI (VW-MRI) in PWH and HIV-uninfected individuals. Design: Cross-sectional study. Methods: We recruited antiretroviral therapy-treated PWH with undetectable plasma viral load and HIV-uninfected individuals. All participants were at least 40 years of age and at moderate-to-high cardiovascular risk. We used Poisson and mixed effects logistic regression models to compare the number and associated characteristics of enhancing intracranial arteries on VW-MRI by HIV status. Results: Of 46 participants (mean age 59 years), 33 were PWH. PWH had nearly four-fold as many enhancing intracranial arteries on VW-MRI than HIV-uninfected individuals (rate ratio 3.94, 95% CI 1.57–9.88, P = 0.003). The majority of wall enhancement was eccentric (76%) and short-segment (93%), suggestive of intracranial atherosclerotic disease (ICAD). Sixty-nine percent of enhancing arteries were not associated with luminal narrowing on magnetic resonance angiography (MRA). None of these characteristics differed significantly by HIV status. Conclusion: In persons at moderate-to-high cardiovascular risk, HIV infection, even when well controlled, may be associated with a greater burden of intracranial large artery disease and, specifically, of ICAD. Studies of the mechanisms underlying higher rates of ischemic stroke in PWH should include evaluation for intracranial large artery disease. VW-MRI provides added value as an adjunct to traditional luminal imaging when evaluating cerebrovascular risk in PWH.